DESIDRATAÇÃO DE CLARAS DE OVOS POR ATOMIZAÇÃO - Grassi, Thiago Luís Magnani; Marcos, Marcelo Tacconi De Siqueira; Cavazzana, Jefferson Felipe; Ponsano, Elisa Helena Giglio (Universidade Federal de Goiás, 2016)
Abstract The aim of this study was to evaluate the yield, microbiological, physical, and chemical characteristics of powdered egg white obtained by spray drying at different temperatures. The spray drying air temperatures were 90 °C, 120 °C, and 150 °C, with five repetitions of each treatment. Yield rate was calculated by the ratio between powdered egg white and fresh egg white. The powdered egg whites were analyzed regarding moisture, protein, lipids, ash, coagulase-positive staphylococci, Salmonella spp, and coliforms at 45 °C. Color analysis was performed with the Lab space and ΔE was calculated from these values. The data were subjected to analysis of variance and Tukeys test at 5% significance. The spray drying air temperature affected the moisture of the powdered egg whites, without influencing the concentrations of proteins, lipids, and ash, nor the microbiological analyzes. The drying at 150 °C provided higher yield rate, but caused the darkening and the increase in the yellowness of the powdered egg white.

Resumo O objetivo deste estudo foi avaliar o efeito de temperaturas de desidratação por atomização sobre o rendimento e as características microbiológicas, físicas e químicas de claras de ovos em pó. Os tratamentos utilizados no experimento foram 90 °C, 120 °C e 150 °C, contando com cinco repetições. O rendimento foi determinado pela relação entre os pesos da clara desidratada e in natura. As claras em pó foram analisadas quanto a umidade, proteínas, lipídeos, cinzas, estafilococos coagulase-positiva, Salmonella spp e coliformes a 45 °C. A análise da cor foi feita no sistema Lab e o ΔE foi calculado a partir desses valores. Os resultados foram submetidos à análise de variância e as médias foram comparadas pelo teste de Tukey, utilizando-se nível de significância de 5%. A temperatura de secagem influenciou a umidade das claras desidratadas mas não interferiu nos teores de proteínas, lipídeos e cinzas e nas características microbiológicas. A secagem a 150 ºC proporcionou maior rendimento mas provocou escurecimento e aumento na intensidade do tom amarelo das claras desidratadas.
EGG WHITE DEHYDRATION BY ATOMIZATION
Keywords: drying; egg products; Maillard reaction; powered egg white; clara em pó; ovoprodutos; reação de Maillard; secagem